THE RELATIONSHIP BETWEEN PARENTING STYLES AND GROWTH AND DEVELOPMENT IN PRESCHOOL CHILDREN - Veronica Silalahi; Marcellina Widayanti; Agung Saputra (Nurse and Holistic Care, 2025)
Background: Preschool is the golden age because children’s growth and development progress very quickly across all aspects. Growth and development are supported by parenting patterns. The phenomenon in the research was that both thin and fat children have not been able to write and draw, have not been able to jump, some children cannot speak with 2 to 6 words, and have not been able to socialize with peers. Related to parenting, still parents who do not give children the opportunity to carry out their tasks, forbid children to play on the grounds of fear of falling, and do not allow children to play outside, other than at home. Objective: The study aims to determine the relationship between parenting patterns and the growth and development of preschool children at PAUD Kemuning Surabaya. Methods: This research design is a correlational study with a cross-sectional approach using a total sampling technique, with a sample size of 40 respondents. Data collection was done using questionnaires and KPSP. Data analysis using Spearman's rank correlation coefficient to determine external variables that influence parenting patterns and growth and development using backward linear regression. Result: The results showed that most of 85% of parenting patterns were democratic, the majority of 90% of respondents had normal height, most of 82.4% had normal weight, and more than 50% (55%) had appropriate developmental. The results of the Spearman Rank test, p=0.390 and p-0,060, indicate that there is no relationship between parenting patterns and growth and development. Conclusion: Some factors influence, such as the number of siblings, parents who work, so that they cannot provide a lot of stimulus for children.